2012
DOI: 10.1016/j.prevetmed.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for farm-level African swine fever infection in major pig-producing areas in Nigeria, 1997–2011

Abstract: African swine fever (ASF) is an economically devastating disease for the pig industry, especially in Africa. Identifying what supports infection on pig farms in this region remains the key component in developing a risk-based approach to understanding the 2 epidemiology of ASF and controlling the disease. Nigeria was used for this matched case-control study, because there is perpetual infection in some areas, while contiguous areas are intermittently infected. Risk factors and biosecurity practices in pig farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 25 publications
7
46
2
1
Order By: Relevance
“…It will therefore be necessary to educate the farmers on the benefits of implementing biosecurity. Fasina et al (2012) in Nigeria found out that it was profitable to implement biosecurity, and such findings could be extrapolated to our study area on the Uganda/ Kenya border. Weaknesses in the implementation of legislative and policy measures severely affected adoption of biosecurity practices by smallholder farmers.…”
Section: Discussionsupporting
confidence: 65%
“…It will therefore be necessary to educate the farmers on the benefits of implementing biosecurity. Fasina et al (2012) in Nigeria found out that it was profitable to implement biosecurity, and such findings could be extrapolated to our study area on the Uganda/ Kenya border. Weaknesses in the implementation of legislative and policy measures severely affected adoption of biosecurity practices by smallholder farmers.…”
Section: Discussionsupporting
confidence: 65%
“…Factors found to increase the risk of outbreak, include free range pig management system [11], the previous occurrence of a disease in the farm [32], the presence of an infected pig farm in the neighbourhood or of an abattoir in the community, and visits by veterinarians and para-veterinarians [33]. A spatial regression analysis found density of the road network, of water bodies and of the domestic swine population to be associated with outbreaks in Russia [34] and a spatial spread model found the movement of infected animals to be the most important factor in the spread of ASFV [35].…”
Section: Reviewmentioning
confidence: 99%
“…The presence of wire mesh coverings on windows on pig houses seemed to protect pigs inside the houses against ASF infection, perhaps because of the effect on reduction of contacts between freeflying birds, rodents or insects and domestic pigs (although these remain unproven means of spread of ASF (Fasina et al, 2012)); and also limits human contact with the pigs. The presence of engorged hard ticks on pigs was positively associated with lower ASF infection.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%